Delivering impact beyond the plate: service quality, information, and government trust in school feeding perception - Sugiharto, Muhammad; Rahma, Rana Ardila; Hadithya, Riyan; Rahmani, Hani Fitria (Jurnal Mantik, 2025)
School feeding programs are widely recognized as strategic interventions to improve child nutrition, support academic achievement, and reduce the economic burden on low-income families, making them a vital component of social policy in many countries, including Indonesia. The Free Nutritious Meal Program for elementary schools aims to address these goals, yet its success depends not only on technical delivery but also on how beneficiaries perceive its benefits. This study examined the perceived benefits of the program by analyzing the influence of food quality, meal distribution frequency, and program information, with trust in government as a mediating variable. Using a quantitative approach, data were collected from 133 parents of beneficiary students through structured questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that food quality has the strongest direct effect on perceived benefits, followed by program information. Meal frequency showed no significant direct effect but contributed indirectly by strengthening trust in government, which emerged as a significant mediator. These findings highlight that improving technical service quality must be accompanied by strategies to build institutional trust. The study offers theoretical contributions by integrating public service management and trust perspectives, and practical implications for policymakers to enhance service quality, transparency, and communication strategies.